Does technology improve reading outcomes? Comparing the effectiveness and cost-effectiveness of ICT interventions for early grade reading in Kenya - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Strigel, Carmen (International Journal of Educational Development, 2016)
Education policymakers are investing in information and communications technology (ICT) without a research base on how ICT improves outcomes. There is limited research on the effects of different types of ICT investments on outcomes. The Kenya Primary Math and Reading (PRIMR) study implemented a randomized controlled trial comparing the effects and cost of three interventions – e-readers for students, tablets for teachers, and the base PRIMR program with tablets for instructional supervisors. The results show that the ICT investments do not improve literacy outcomes significantly more than the base non-ICT instructional program. Our findings show that cost considerations should be paramount in selecting ICT investments in the education sector.
EdTechHub.Copy: 2129771:QHYYISLI shortDOI: 10/f8t8wn KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2016.03.006 10/f8t8wn 2129771:QHYYISLI 2339240:45CT95ZX 2339240:59F29QUS 2339240:AKA34H48 2339240:ERJRDYGR 2339240:JWWGS2FM 2339240:VHERHC8U 2339240:W2IRHE4N 2405685:6GPCWMKY 2405685:DH6QGZK3 2405685:DSJ268AF 2405685:HNU98RFR 2405685:NAH85KGQ 2405685:RJ64GDLT 2405685:T6BQBZK6 2405685:Y3YWXGDF 2534378:DA5UA4C3 2534378:IQ2QU9ZM 2534378:NFIYL9F6
Keywords: Education policy; International education; Kenya; Literacy; Reading; Technology; __:import:01; __:match:final; __:matched; __:study_id:2457283; ___working_potential_duplicate; __finaldtb

Cost-Effectiveness and Affordability of Interventions, Policies, and Platforms for the Prevention and Treatment of Mental, Neurological, and Substance Use Disorders - Levin, Carol; Chisholm, Dan (Mental, Neurological, and Substance Use Disorders: Disease Control Priorities, 2016)
Since the turn of the millennium, considerable progress has been made in developing an evidence base on which interventions are effective and feasible for improving mental health in low- and middle-income countries (LMICs). Such evidence provides a critical input to the formulation of plans and priorities to address the large and growing burden of mental, neurological, and substance use (MNS) disorders. However, for successful and sustainable scale-up of effective interventions and innovative service delivery strategies, decision makers require not only evidence of an intervention’s impact on health and other outcomes, such as equity or poverty, but also evidence of its cost and cost-effectiveness. Cost data provide information relevant to the financial planning and implementation of prioritized, evidence-based strategies; cost-effectiveness analysis indicates the relative efficiency or value for money associated with interventions or innovations. The application of economic evaluation to MNS disorders has largely focused on the assessment of a specific intervention’s costs and health outcomes, relative to some comparator, which may be treatment as usual, another innovation, or no intervention. Such assessments have often been conducted alongside clinical trials, enabling health economic researchers to add resource use questions to study protocols, generate estimates of each trial participant’s health care costs, and relate these costs to primary outcome measures in the form of cost-effectiveness ratios. We review this type of economic evidence over the course of this chapter, with a particular focus on studies that have been successfully carried out in LMICs. However, the number of completed studies remains small and insufficient to inform resource allocation decisions in all the national settings where cost-effectiveness information would be valuable, including the many countries where informal or traditional health care represents the predominant model of service availability. This paucity of economic evidence reflects the overall lack of resources and infrastructure for mental health services in LMICs, including research capacity. Partly to address the paucity of cost-effectiveness trials, as well as their intrinsic specificity to the setting in which they are conducted, a broader, modeling-based approach has also been used to build up economic evidence for international mental health policy and planning. This approach includes the earlier editions of the Disease Control Priorities (DCP) project and the World Health Organization’s (WHO) CHOosing Interventions that are Cost-Effective (CHOICE) project. Such model-based studies rely on existing data, as well as several analytical assumptions; these studies have adopted an epidemiological, population-based approach that identifies the expected costs and health impacts of delivering evidence-based interventions at scale in the population as a whole, whether a specific country or an entire region. We also review this form of economic evidence and comment on important gaps in the current evidence base, as well as the relative strengths and limitations of this approach. One important limitation of conventional cost-effectiveness analysis—whether garnered through trial-based or model-based approaches—is that it is restricted to consideration of the specific implementation costs and health-related outcomes of an intervention; it does not typically extend to the nonhealth or wider economic or social value of investing in mental health innovation and service scale-up. In particular, cost-effectiveness analysis in its conventional form has little to say about the equitable distribution of costs and health gains across different groups of the target population. Incorporation of such concerns into economic evaluation represents a major objective of extended cost-effectiveness analysis, which is explored and addressed specifically in chapter 13 in this volume (Chisholm, Johansson, and others 2015). In this chapter, we review the available cost-effectiveness evidence for the different levels and underpinning strategies of the mental health care system, with a focus on information generated in or for LMICs. Based on the overall analytical framework and priority intervention matrices developed for this volume, the remainder of the chapter is presented as follows. First, we consider the economic evidence for mental health prevention and protection at the population and community levels of the health and welfare system, including legislative, regulatory, and informational measures at the public policy level (population platform), as well as school-, workplace-, and community-based programs (community platform). We then examine the economic evidence relating to the identification and treatment of MNS disorders (health care platform), focusing on the relative cost-effectiveness or efficiency of treatment programs implemented in nonspecialized versus more specialized health care settings. Finally, we assess the financial costs and budgetary implications of implementing or scaling up a set of prioritized, cost-effective interventions. Our review is based on available, published literature. A systematic search of the literature for LMICs was undertaken in PubMed to find articles published since 2000 in English. The search combined terms for specific mental health interventions with economic terms such as “cost,” “cost-effectiveness,” or “quality-adjusted life year (QALY),” as well as the names of all LMICs and their respective regions (see annex 12A for a list of search terms used to identify relevant literature). Where little or no literature was found for LMICs on interventions of potential importance, this systematic search was augmented by selective searches of the literature available since 1995 for high-income countries (HICs); however, these results are not included in the figures or tables. Annex 12B provides the search statistics. Articles included in the review were graded using the checklist of Drummond and others (2005) to generate a quality score for each article, with most studies graded between 7 and 10. Annex 12C provides a list of studies that were used to generate the tables and figures presented in this chapter. It presents detailed information on the intervention characteristics and comparators, target population group, geographic location, methodology, results, and quality scores. All cost-effectiveness results are presented in 2012 US$ except where noted otherwise. Consistent with earlier iterations of DCP, reported regional estimates refer to the World Bank’s categorization of countries by income.
KerkoCite.ItemAlsoKnownAs: 2339240:MMWPL7JY 2405685:NEXA5KQM

SmartIT: Total Cost of Ownership Assessment - Consortium for School Networking (2016)
KerkoCite.ItemAlsoKnownAs: 2339240:JD9MQENJ 2405685:FVTSMWDW

QALY-based cost-effectiveness analysis - Pinto-Prades, J. L; Herrero, C; Abellán, J. M (The Oxford Handbook of Well-Being and Public Policy, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:XLRKBCZ4

The rise and fall of the PC in one chart - Booton, Jennifer (MarketWatch, 2016)
Section: Industries KerkoCite.ItemAlsoKnownAs: 2339240:USFBBPHB 2405685:D94GQ9W9

Tangerine® – Mobile Learning Assessments Made Easy - RTI International (RTI, 2016)
Since 2010, improving early grade reading has been a top priority for RTI and for many bilateral and multilateral donors, including the U.S. Agency for International Development (USAID), The World Bank, UK Aid and others. In support of this work and to improve upon paper forms of assessment, RTI developed a mobile assessment and coaching tool we dubbed Tangerine. Open source for all users, Tangerine is a first-of-its-kind software application optimized for offline data collection on low-cost Android tablets.
Library Catalog: www.rti.org EdTechHub.ItemAlsoKnownAs: 2405685:S8WJWDX2

The cascade model of teachers’ continuing professional development in Kenya: A time for change? - Bett, Harry Kipkemoi (Cogent Education, 2016)
Kenya is one of the countries whose teachers the UNESCO (2015) report cited as lacking curriculum support in the classroom. As is the case in many African countries, a large portion of teachers in Kenya enter the teaching profession when inadequately prepared, while those already in the field receive insufficient support in their professional lives. The cascade model has often been utilized in the country whenever need for teachers’ continuing professional development (TCPD) has arisen, especially on a large scale. The preference for the model is due to, among others, its cost effectiveness and ability to reach out to many teachers within a short period of time. Many researchers have however cast aspersions with this model for its glaring shortcomings. On the contrary, TCPD programmes that are collaborative in nature and based on teachers’ contexts have been found to be more effective than those that are not. This paper briefly examines cases of the cascade model in Kenya, the challenges associated with this model and proposes the adoption of collaborative and institutionbased models to mitigate these challenges. The education sectors in many nations in Africa, and those in the developing world will find the discussions here relevant.
shortDOI: 10/gfw2mk KerkoCite.ItemAlsoKnownAs: 10.1080/2331186X.2016.1139439 10/gfw2mk 2405685:K8ZKUDQE

Influence of mobile learning training on pre-service social studies teachers' technology and mobile phone self-efficacies - Gloria, Adedoja; Oluwadara, Abimbade (Journal of Education and Practice, 2016)
Current instructional deliveries favour the use of mobile technology because of its inherent potentials and benefits such as portability, ease of use cost and others. Despite these benefits, many teachers especially in Sub-Saharan Africa still prefer the conventional method and use mobile phones for social engagements such as texting, chatting, callings and others. Though, these teachers use mobile phones for these social activities, using it for instruction is somewhat problematic for them without adequate training on its pedagogical implications. This is also because there are dearth of trainings in this area. Some factors that could however affect this type of specialised training include Technology Self-efficacy, Mobile Phone Self-efficacy, attitude, age and others. The sample of this present study was 101 pre-service social studies teachers in two Universities in Nigeria. The influence of the Mobile learning training on Technology/Mobile Phone Self-efficacies was explored. The results indicated that the pre-service social studies teachers have high Technology/Mobile Phone Self-efficacies after exposure to the training.
Publisher: IISTE, No 1 Central, Hong Kong Island, Hong Kong SAR KerkoCite.ItemAlsoKnownAs: 2405685:2B3XKEGJ 2405685:MNN95GGK 2534378:GD8S4UHN 2534378:KAL73UF6 2534378:SDN92DUR
Keywords: Age Differences; ERIC; Current Index to Journals in Education (CIJE); Electronic Learning; Foreign Countries; Higher Education; Instructional Effectiveness; Likert Scales; Nigeria; Postsecondary Education; Predictor Variables; Preservice Teachers; Pretests Posttests; Questionnaires; Self Efficacy; Social Studies; Student Teacher Attitudes; Technological Literacy; Technology Education; __:import:01; __:match:final; __:matched; __:study_id:2096188; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets